The Completion of Non-Performing Loans in Financial Technology Peer to Peer Lending - Adi Sudharma, Kadek Januarsa; Kurniawan, I Gede Agus; Sihombing, Mario Binsar Martua (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 3 (2023), 2023)
This study aimed at defining the forms of disputes resolution conducted by the parties involved in peer to peer lending fintech business.  article aims to analyze the forms of dispute resolution that can be taken by the parties in the peer to peer lending fintech business. This article uses normative legal research with statutue approach. The results show that the parties in the dispute on bad loans in the Peer to Peer Lending Fintech business can take two forms of dispute resolution, namely litigation and non-litigation. The litigation route is to file a simple lawsuit or by Parate Executie, while through the non-litigation route, it could yo use the Alternative Dispute Resolution Institution for the Financial Service Sector.